High Prevalence of Hepatitis E Virus in Wild Boar (Sus scrofa) in Yamaguchi Prefecture, Japan - Hara, Yuka; Terada, Yutaka; Yonemitsu, Kenzo; Shimoda, Hiroshi; Noguchi, Keita; Suzuki, Kazuo; Maeda, Ken (Journal of wildlife diseases, 2014)
Hepatitis E virus (HEV) causes a food- and water-borne disease in humans, and Japanese wild boar (Sus scrofa leucomystax) meat is one of the most important sources of infection in Japan. We tested 113 serum samples from wild boar captured in Shimonoseki City, Yamaguchi Prefecture, Japan from 2010 to 2012. Serum samples were tested by enzyme-linked immunosorbent assay (ELISA) using virus-like particles as antigen and nested reverse-transcription PCR (RT-PCR). Anti-HEV IgG antibodies were detected in 47 of the 113 wild boar serum samples (42%), and HEV RNA was detected in five samples (4%). Sequence analysis showed that the five HEV isolates belonged to genotype 4, forming a cluster with a previous isolate from a human hepatitis E case in this region in 2011. These results indicate that wild boar in this region are infected with potentially pathogenic HEV at a high prevalence.